Some problems of creation of modern astronomical television measuring systems - Strygin, N. Z.; Prokof’eva, V. V.; Sukhov, P. P.; Karpenko, G. F. (Одеські астрономічні публікації, 2017)
About some problems of creation of modern astronomical television measuring systems